Community Perception of Mobile Payment in e-Government Services - Ahsan, A.; Chang, Vanessa; Issa, Tomayess (ACIS, 2012)
Mobile payment and e-Government are emerging topics in the research area of Information Systems. This research addresses the preferred e-Government services for mobile payment, the suitable payment methods of mobile payment, and adoption factors of e-Government services. The research derives the notion of technology adoption and related constructs, however, as no particular Information Systems adoption theory was adequate to study emerging systems of electronic payment, the research did not utilise any specific theory. Rather, the research uses the characteristics of mobile payment as revealed in the contemporary research to develop an adoption model based on user perceptions regarding mobile payments in the context of e-Government services. A survey study on the use of mobile devices to pay for e-Government services was conducted in Western Australia. The findings of this research contribute conceptually and practically by recommending suitable services and mobile payment methods. This paper also addresses the positive and negative factors impacting the adoption of mobile payment for e-Government services.